Aquatic insect communities in headwater streams of Ciliwung River watershed, West Java, Indonesia - Wakhid Wakhid; Aunu Rauf; Majariana Krisanti; I Made Sumertajaya; Nina Maryana (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wakhid, Rauf A, Krisanti M, Sumertajaya IM, Maryana N. 2021. Aquatic insect communities in headwater streams of Ciliwung River watershed, West Java, Indonesia. Biodiversitas 22: 30-41. Ciliwung is one of the major rivers flowing from Cisarua (Bogor) to Jakarta. This study was conducted to assess and compare aquatic insect biodiversity and community structure in various headwater streams with respect to different land-use types. Ten stream reaches of the first and second orders representing three different land-use types in the surrounding area (forest, tea plantation, village) were selected. At each stream reach, the aquatic insects were collected using a D-net (0.4 mm mesh). Physico-chemical properties of water were directly measured in the field. Samples were collected every two months from April until December 2018. A total of 26531 aquatic insect specimens belonging to 75 species/morphospecies, 46 families, and 10 orders were recorded. The order Trichoptera was the most abundant comprising 51.28% of the total collected insects, followed by Diptera (30.5%), Ephemeroptera (7.52%), and Plecoptera (6.25%). The highest proportion of functional feeding group was filtering-collectors (61.34%), followed by shredders (16.29%), gathering-collectors (15.32%), and predators (6.94%). Abundance of Diptera and Plecoptera was significantly higher in forest streams, while Ephemeroptera in plantation streams, and Trichoptera in village streams. The peak population of Diptera, Ephemeroptera, and Trichoptera occurred in June (dry period), while Plecoptera in December (wet period). The forest streams exhibited the highest species richness and diversity. Analysis of similarity (ANOSIM) showed a low dissimilarity among streams of the three land uses (Global R=0.217; P<0.001). The non-metric multidimensional scaling (NMDS) analysis showed that forest streams somewhat separated from plantation and village streams. The study provided important information on aquatic insect biodiversity, and indicated the need for forest area preservation in the headwater streams of Ciliwung River watershed.